The evaluation of efficacy of Ahmed valve implantation in the surgical treatment of glaucoma in children and adolescents - Bakunowicz-Łazarczyk, Alina; Urban, Beata (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To report the safety and efficacy of Ahmed glaucoma valve implantation in the management of secondary glaucoma in children and adolescents. Material and methods: 6 patients with secondary glaucoma underwent Ahmed valve implantation. 1 patient had aphakic glaucoma, 3 patients had traumatic glaucoma, 1 patient had aniridia and 1 patient had ectropion uveae. IOP values range from 35 to 51 mmHg (mean 41.3 mmHg), with maximal medical treatment by this time. Mean follow-up was 2.17 years. Results: Mean pooperative IOP ranged from 2 to 8 mmHg (mean 6 mmHg), during the first week. 6 months later IOP increased to 15.2 (6-21) mmHg. The mean IOP at last follow-up was 15 mmHg and overall success rate was 83.3%. We observed one hypotony, one tube exposure and one Tenon’s cyst formation. Conclusions: The Ahmed valve is effective treatment for secondary glaucoma in children. It can be useful to avoid enucleation of the eye with traumatic glaucoma.